CAN SOCIAL CONSTRUCTIVISM IN IR SHAPE FOREIGN POLICIES? A CASE OF NORTH KOREA-CHINA RELATIONS - Mukhia, Anmol (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2025)
From time to time, North Korea and China’s relations have been analyzed by different scholars as a byproduct or satellite state of China. We often debate power, war, and allies from a realist understanding. However, the constructivist approach has not been addressed much. The significant developments during the Korean War were symbolic, shared ideas, and the creation of identities, which were crucial to understanding the state’s choice and preference in foreign policy decision-making. In this article, I draw on the work of the constructivist approach to argue the North Korean and China relations during the Korean War. In this way, the constructivist explanation can be suitable for explaining the dynamics of North Korean and China ties because they look at the history and social dynamics within states for its outcome.